EVALUATION OF ADENOIDS BY ORONASAL AND NASAL SPIROMETRY - R, Gayatri Devi; G, Sethu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The main aim of this study is to compare the oronasal and nasal spirometry among adenoid hypertrophy children before and after surgery. Methods: A total of 40 healthy and 40 adenoid hypertrophy children were recruited for this study with the age range from 6 to 15 years. All the children were examined by two measurements (1) oronasal spirometry and (2) nasal spirometry. Forced vital capacity (FVC), forced expiratory volume in 1 s (FEV 1), FEV 1/FVC%, forced expiratory time (FET), peak expiratory flow rate, peak inspiratory flow rate (PIFR), and forced expiratory flow (FEF)25-75, FEF25%, FEF50%, FEF75%, FIF25%, FIF50%, and FIF75% were recorded. Results: All the parameters were significantly reduced in adenoid hypertrophy by nasal spirometry when compared to oronasal spirometry. FEV1/ FVC% was insignificant from oral to nasal values among adenoid hypertrophy in both the sexes. FET can act as an indicator for upper airway obstruction which shown significantly in adenoid hypertrophy but insignificant among control and adenoidectomy. Inspiratory parameters also had shown more variation in nasal than oronasal spirometry. Conclusion: Significant differences were found in many parameters between oronasal and nasal spirometry among adenoids and adenoidectomy. Nasal spirometry is a portable one, simple, and less cost-effective and so it can be used to determine the obstruction in the nose nasopharynx region.